Transatlantic secondary contact in Atlantic Salmon, comparing microsatellites, a single nucleotide polymorphism array and restriction‐site associated DNA sequencing for the resolution of complex spatial structure. Issue 20 (October 2015) - Bradbury, Ian R.; Hamilton, Lorraine C.; Dempson, Brian; Robertson, Martha J.; Bourret, Vincent; Bernatchez, Louis; Verspoor, Eric
Abstract Identification of discrete and unique assemblages of individuals or populations is central to the management of exploited species. Advances in population genomics provide new opportunities for re‐evaluating existing conservation units but comparisons among approaches remain rare. We compare the utility of RAD‐seq, a single nucleotide polymorphism (SNP) array and a microsatellite panel to resolve spatial structuring under a scenario of possible trans‐Atlantic secondary contact in a threatened Atlantic Salmon, Salmo salar, population in southern Newfoundland. Bayesian clustering indentified two large groups subdividing the existing conservation unit and multivariate analyses indicated significant similarity in spatial structuring among the three data sets. mtDNA alleles diagnostic for European ancestry displayed increased frequency in southeastern Newfoundland and were correlated with spatial structure in all marker types. Evidence consistent with introgression among these two groups was present in both SNP data sets but not the microsatellite data. Asymmetry in the degree of introgression was also apparent in SNP data sets with evidence of gene flow towards the east or European type. This work highlights the utility of RAD‐seq based approaches for the resolution of complex spatial patterns, resolves a region of trans‐Atlantic secondary contact in Atlantic Salmon in Newfoundland and demonstrates the utility of multiple marker comparisons in identifying dynamics of introgression.